Integrating the Hallmarks of Aging Throughout the Tree of Life: A Focus on Mitochondrial Dysfunction - van der Rijt, Sanne; Molenaars, Marte; McIntyre, Rebecca L.; Janssens, Georges E.; Houtkooper, Riekelt H. (Frontiers in Cell and Developmental Biology, 2020)
Since the identification and definition of the hallmarks of aging, these aspects of molecular and cellular decline have been most often described as isolated or distinct mechanisms. However, there is significant evidence demonstrating interplay between most of these hallmarks and that they have the capacity to influence and regulate one another. These interactions are demonstrable across the tree of life, yet not all aspects are conserved. Here, we describe an integrative view on the hallmarks of aging by using the hallmark “mitochondrial dysfunction” as a focus point, and illustrate its capacity to both influence and be influenced by the other hallmarks of aging. We discuss the effects of mitochondrial pathways involved in aging, such as oxidative phosphorylation, mitochondrial dynamics, mitochondrial protein synthesis, mitophagy, reactive oxygen species and mitochondrial DNA damage in relation to each of the primary, antagonistic and integrative hallmarks. We discuss the similarities and differences in these interactions throughout the tree of life, and speculate how speciation may play a role in the variation in these mechanisms. We propose that the hallmarks are critically intertwined, and that mapping the full extent of these interactions would be of significant benefit to the aging research community.